Metals by Micro‐Scale Additive Manufacturing: Comparison of Microstructure and Mechanical Properties - Reiser, Alain (Adv Funct Mater, 2020)
Many emerging applications in microscale engineering rely on the fabrication of 3D architectures in inorganic materials. Small‐scale additive manufacturing (AM) aspires to provide flexible and facile access to these geometries. Yet, the synthesis of device‐grade inorganic materials is still a key challenge toward the implementation of AM in microfabrication. Here, a comprehensive overview of the microstructural and mechanical properties of metals fabricated by most state‐of‐the‐art AM methods that offer a spatial resolution ≤10 μm is presented. Standardized sets of samples are studied by cross‐sectional electron microscopy, nanoindentation, and microcompression. It is shown that current microscale AM techniques synthesize metals with a wide range of microstructures and elastic and plastic properties, including materials of dense and crystalline microstructure with excellent mechanical properties that compare well to those of thin‐film nanocrystalline materials. The large variation in materials' performance can be related to the individual microstructure, which in turn is coupled to the various physico‐chemical principles exploited by the different printing methods. The study provides practical guidelines for users of small‐scale additive methods and establishes a baseline for the future optimization of the properties of printed metallic objects—a significant step toward the potential establishment of AM techniques in microfabrication.